Diversity of Bacterial Community in the Oxygen Minimum Zones of Arabian Sea and Bay of Bengal as Deduced by Illumina Sequencing - Fernandes, Genevieve L.; Shenoy, Belle Damodara; Damare, Samir R. (Frontiers in Microbiology, 2020)
The Indian Ocean harbors oxygen minimum zones (OMZs) in the Arabian Sea and Bay of Bengal, with dissolved oxygen < 20 μM, located at the mid-depths of the water column. Till date, high-throughput sequence-data on depth-wise distribution of prokaryotic communities have rarely been reported from these OMZs. The present study aimed to characterize the prokaryotic diversity inhabiting Arabian Sea Time Series (ASTS) and India’s Idea 2 (II2) in the Arabian Sea, and Bay of Bengal Time Series (BoBTS) in the Bay of Bengal OMZs based on amplicon sequencing of 16S rRNA gene regions, along 6 sampled depths in the water column. High prokaryotic richness was observed in the Arabian Sea and Bay of Bengal samples. Operational taxonomic units (OTUs) in the range of 1249–3298 were identified, wherein, less prokaryotic diversity was observed at surface and within oxygen minimum depths. At phylum level, most OTUs were affiliated to Bacteroidetes, Chloroflexi, Cyanobacteria, Marinimicrobia, Planctomycetes and Proteobacteria. Prokaryotic community differed between ASTS, II2 and BoBTS locations along varying physicochemical conditions. Predictive functional profiling of the bacterial communities suggested the involvement of abundant microbes in nitrogen and sulphur metabolism pathways. Bacterial isolates belonging to genera from the clades, δ-Proteobacteria and γ-Proteobacteria, described previously for their participation in biogeochemical cycling of N-and-S in the OMZs were reported from deoxygenated waters of both the basins. Bacteria involved in anammox such as Candidatus Scalindua were found to be relatively high at ASTS and II2 locations in the Arabian Sea. Further studies are required to ascertain the role of abundant bacteria along the dynamic oceanographic processes in the OMZs.